Effect of waist-to-hip ratio on the association between type 2 diabetes and depression: an exploratory study using the polygenic scores approach in the UK Biobank. (23rd February 2017) - Kan, Carol; Coleman, Jonathan; Mahajan, Anubha; McCarthy, Mark; Breen, Gerome; Ismail, Khalida; Lewis, Cathryn; ,
Abstract: Background: A genetic overlap between type 2 diabetes and depression has been reported in twin studies, but the finding has not been replicated with data from genome-wide association studies. Visceral adiposity has been postulated as being on the causal pathway of the association between type 2 diabetes and depression. Since waist-to-hip ratio can be a proxy measure of intra-abdominal fat deposition, we examined its effect on the association using the polygenic scores approach in the UK Biobank. Methods: Type 2 diabetes polygenic scores were constructed from the association summary statistics of the Diabetes Genetic Replication And Meta-analysis Consortium, and depression polygenic scores from the Psychiatric Genetics Consortium Major Depressive Disorders Workgroup (29 studies at seven association p-value thresholds [p=0·001 to p=0·5). Logistic regression examined the association between type 2 diabetes polygenic scores and depression case-control status and the effect of body-mass index (BMI)-adjusted waist-to-hip ratio on the association, adjusting for ancestry, centres, and genotyping batches. Findings: The UK Biobank sample with genotyping data consisted of 152 551 participants. There were 10 005 cases and 19 314 controls for depression among individuals of European ancestry, with a mean age of 57·1 years (SD 7·8), BMI of 27·5 kg/m 2 (4·7), and waist-to-hip ratio of 0·88 (0·09). Type 2 diabetes polygenic scores were not predictive of depression case-status at all p-value thresholds examined. The interaction between waist-to-hip ratio and type 2 diabetes polygenic scores had an effect on depression case-status (at p-value threshholds <0·2, β=0·37, p=0·02). Interpretation: Our exploratory study tentatively suggests that waist-to-hip ratio might have a role in the effect of type 2 diabetes polygenic scores on depression case-status. Higher adiposity is associated with greater level of inflammation, which is in turn associated with increased risk of type 2 diabetes and depression. Further research is needed to determine the direction of causation and to replicate our finding, given the cross-sectional design and the proxy use of waist-to-hip ratio for visceral adiposity. Funding: Novo Nordisk UK Research Foundation.